Reentrant condensation of proteins in solution induced by multivalent counterions. - Zhang, F; Skoda, M; Jacobs, R; Zorn, S; Martin, R; Martin, C; Clark, G; Weggler, S; Hildebrandt, A; Kohlbacher, O; Schreiber, F (2008)
Negatively charged globular proteins in solution undergo a condensation upon adding trivalent counterions between two critical concentrations C and C, C